Job satisfaction and turnover in the Chinese retail industry - Tian, Amy (Emerald Group Publishing, 2009)
Purpose – The purpose of this paper is to investigate employee turnover in a leading Chinese retail organisation, where high turnover rates are recognised as being a major issue for human resource strategy. The study seeks to focus on the job satisfaction-turnover relationship, examining how this is moderated by occupation. Design/methodology/approach – A literature review on employee job satisfaction and employee turnover provides the basis for the research model and hypotheses. A self-completion questionnaire survey, involving 164 respondents (95.4 per cent response rate) from a leading Chinese retail organisation was used to gather data and test existing theory in a Chinese context. Findings – The results provided strong support for the hypothesised negative relationship between employee turnover intention and job satisfaction. Occupation is also significantly associated with job satisfaction, turnover intention and the job satisfaction-turnover relationship: non-management/frontline employees expressed higher levels of intention to leave their job than management/office employees. Research limitations/implications – The sample was limited to one retail organisation in China. It may not be appropriate to generalise the findings across other populations or settings. However, the sample can be viewed as a representative case typical of many other organisations in the same industry. Practical implications – The results provide insight into the impact of employee job satisfaction on turnover intention in the particular Chinese retail setting which could benefit managers and policy makers in the focus organisation as well as other organisations operating in the same sector in general.